The use of artificial intelligence technology in learning and its impact on the role of teachers in the future: Systematic review - Dherkha Mursal (University of Muhammadiyah Malang, 2026)
Background: The integration of Artificial Intelligence (AI) in education is revolutionizing educational workflows and reshaping the role of educators. AI technologies offer significant potential to enhance personalized learning, streamline administrative tasks, and support curriculum design. However, their adoption raises critical challenges and implications for daily instruction. Objectives: This study aims to explore the impact of AI on learning outcomes and the evolving role of teachers, focusing on how AI can complement educational practices without undermining the human aspects of teaching. Methods: A systematic review of literature was conducted, analyzing 5 selected articles published between 2017 and 2024 to evaluate AI applications in education, emphasizing both its advantages and potential drawbacks. Results: The findings reveal that AI enhances personalized learning by tailoring educational content to individual student needs, automating routine tasks, and providing actionable insights through data analytics. However, challenges such as ethical concerns, technological dependency, and the necessity of professional development for educators persist. Conclusions: While AI offers transformative opportunities, it cannot replace the unique human capabilities of teachers in fostering critical thinking, creativity, and emotional intelligence. As a systematic literature review, this study concludes by recommending targeted training programs and strategic policies to ensure AI serves as a collaborative tool, enhancing rather than replacing traditional teaching roles.